#TITLE_ALTERNATIVE# - NUR RACHMAN (NIM : 223 09 304), ASEP
Microearthquake occurred due to hydraulic fracturing during well injection processes in the Malabar complex. The microearthquake monitoring have been done for 44 days and obtained selected 216 events with high to noise ratio signal. We used these data to invert for velocities structure using double-difference tomography (TomoDD) method in this study. We improved P-and S-wave arrival times phases by applying waveform cross-correlation method (WCC) as input for TomoDD inversion. For the WCC processes, we selected a master event for each station and then the slave events are alignment. The tomographic inversion results show low Vp, low Vs, and high Vp/Vs ratio of 1.85 at depth of about 1.5 km close to edge of the well injection that may be associated with water content from the well. The high Vp/Vs value of water content in this region seems to have North-East direction. The relocated hypocenters show more concentrated around the local faults.